Building The Resilience of Enterprises Through Financial Insurance: The Scale and Dynamics of The Phenomenon in Poland - Karina OLEJNICZAK; Agnieszka KURDYŚ-KUJAWSKA (Communications of International Proceedings, 2023)
Business activities involve high risk. Nowadays, in times of many challenges emerging at the same time, financial risk is becoming particularly important in business. Its implementation may have serious consequences for the further functioning of the company, reducing the overall resilience of companies to emerging challenges. Entrepreneurs take various actions to reduce financial risk, including the transfer of risk to an insurance institution. The aim of our study is to determine the scale and dynamics of changes in the use of financial insurance by Polish companies in the context of building their resilience. The research used literature studies and reports from the Polish Financial Supervision Authority. The analysis covers the years 2010-2021. Over the last decade, the importance of financial insurance in business risk management has been increasing. The increase in the number of financial insurance contracts means increased protection in the event of inability to repay a loan, loss of profits, or reduced risk in the event of contractors' insolvency. Entrepreneurs mostly purchased insurance for various financial risks and used insurance guarantees to a lesser extent. The number of financial insurance benefits paid increased threefold in the analyzed period. In turn, the value of claims settled (paid) under financial insurance decreased. Similar trends were visible for the average value of compensation paid.
Keywords: financial resilience; financial insurance; enterprise; Poland